Construction of internal electric field in imprinted poly (ionic liquid)-TiO2 composite nanoreactor for improving hole directional enrichment and selective photodegradation. (29th September 2022) - Zhou, Guosheng; Yan, Huan; Ren, Yewei; Song, Minshan; Hang, Ying; Liu, Xinlin; Li, Chunxiang; Han, Song; Chen, Ziran; Lu, Ziyang
Abstract: In this work, imprinted poly (ionic liquid)-TiO2 composite nanoreactor (I-PIL-TiO2 ) was synthesized by the microwave-assisted in-situ polymerization in non-toxic aqueous phase. The S-scheme heterojunction made of I-PIL wrapping TiO2 had a tight and large interface region. According to Mott–Schottky's experiment and theoretical calculation, the obtained composite nanoreactor had improved the rapid separation and migration of carriers and increased carrier density, which was closely related to the formation of internal electric field (IEF) driven channels in the interface. The results showed that the orientation of the IEF was from TiO2 to I-PIL, so that photogenerated holes (h + ) were accelerated to migrate to I-PIL through the interface channel, which was conducive to h + directly attacking LEV. The photocatalytic activity of I-PIL-TiO2 was 1.69 times higher than that of TiO2 . More interestingly, the presence of IEF increased the enrichment ability of h + in imprinted cavities, improved the selective degradation ability of the composite nanoreactor, and maintained stable performance in the swine wastewater. After five degradation reactions, the composite still maintained good stability. This work provided a feasible way to synthesize polymer-inorganic composite photocatalytic materials with good interfacial charge transfer by simple and green method. Graphical abstract: Construction of internal electric field at the interface of imprinted poly (ionic liquid)-TiO2 composite nanoreactor by microwave-assisted in-situ polymerization for improving hole directional enrichment and selective photodegradation of levofloxacin. Image 1